Boosting Islamic Banking Market Share in Indonesia: Prioritized Strategies - Rulindo, Ronald; Hidayat, Sutan Emir; Rifqi, Muhammad; Istiqomah, Ratih (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2024)
In Indonesia, despite having the necessary infrastructure, the Islamic banking sector holds only a 7% market share after 30 years. This study, utilizing the Analytic Hierarchy Process (AHP) with experts from various fields, aims to identify and prioritize strategies to enhance the market share of Islamic banking. The findings highlight three key strategies: first, enhancing regulatory support for Islamic banks; second, cultivating skilled human capital and advancing knowledge in Islamic finance; and third, improving Islamic economic literacy among stakeholders Abstrak:Di Indonesia, meski memiliki infrastruktur yang memadai, sektor perbankan syariah hanya menguasai 7% pangsa pasar setelah 30 tahun. Penelitian yang memanfaatkan Analytic Hierarchy Process (AHP) dengan para ahli dari berbagai bidang ini bertujuan untuk mengidentifikasi dan memprioritaskan strategi untuk meningkatkan pangsa pasar perbankan syariah. Temuan ini menyoroti tiga strategi utama: pertama, meningkatkan dukungan peraturan bagi bank syariah; kedua, menumbuhkan sumber daya manusia yang cerdas dan memajukan ilmu pengetahuan di bidang keuangan syariah; dan ketiga, meningkatkan literasi ekonomi syariah di kalangan pemangku kepentingan.